Aspirin Resistance and Its Importance - Aru W Sudoyo (Acta Medica Indonesiana, 2016)
The use of salicylates (popularly known as aspirin or ASA) is well established for the secondary prevention of cardiovascular disease. However, there are reportedly a numer of patients who suffered repeat cardiovascular events despite being given aspirin “prophylaxis”, and uncertainty prevails on whether or not this is due to an inherent inability of aspirin to sufficiently modify platelet activity or are there other mechanisms involved. Coined as “aspirin resistance”, the condition warrants attention as an ineffective prophylaxis may lead to unexpected morbidity and subsequent disappointment